IMPELENTASI MODEL BRAIN BASED LEARNING BERBASIS TRI HITA KARANA UNTUK MENINGKATKAN KARAKTER BERKEBHINEKAAN GLOBAL SISWA SEKOLAH DASAR - candra prastya; I Wayan Suja; Wayan Sutajaya (Yayasan Hurriah, Banda Aceh, 2022)
The rapid development of technology has both positive and negative impacts. One of the negative impacts is the occurrence of moral degradation which is indicated by the behavior of respecting culture which seems to be decreasing. this behavior shows the low character of students with global diversity. Therefore it is necessary to find a solution to improve the character of Global Diversity, namely by implementing the Tri Hita Karana-based Brain Based Learning model. This type of research is classroom action research (PTK). The research subjects were 28 grade IV students at SDN 1 Banyuasri. Primary data was collected by giving students a global diversity character questionnaire consisting of 20 statement items as measured by a Likert scale. Meanwhile, secondary data was obtained through a literature search and previous research. The results showed that there was an increase in the diversity character scores from cycle I to cycle II. So it means that the implementation of the Tri Hita Karana-based Brain Based Learning Model can improve the global diversity character of fourth grade students at SDN 1 Banyuasri